"ZIJ-I SULTANI" IN THE SCIENTIFIC ACTIVITY OF ULUGH BEG - Hamdamov Islоm Akramovich (Journal Park Publishing, 2022)
At a time when there is a struggle for human consciousness in the international arena, it is important to pay attention to the advanced and creative ideas of encyclopaedic scientists, to study and promote them. In particular, the perspective of the nation and the country, behind which the future of our country, depends on the youth, and in the upbringing of such a generation, the spiritual heritage of the great thinker Ulugh Beg, life experience, suitable for all times, reflects the spiritual and moral development of a person, and their scientific and philosophical analysis today, the morality of society should be seen as an objective necessity in solving problems. This article will pay attention to the scientific heritage of the statesman and great scientist Ulugh Beg, who carried out social changes in society and people's lives through the development of science and culture, including scientific and philosophical issues outlined in the work "Zij-i Sultani".
Keywords: madrasa, Ulugh Beg, Kazi-zade ar-Rumi, Ali Qushji